Neoadjuvant Radiochemotherapy Followed by Curative Resection in Patients with Advanced Non-Small Cell Lung Cancer in Stage IIIA/IIIB: Prognostic Factors and Results - Schreiner, Waldemar; Dudek, Wojciech; Lettmaier, S.; Gavrychenkova, S.; Rieker, R.; Fietkau, Rainer; Sirbu, Horia (Zentralblatt für Chirurgie, 2016)
The role of surgical lung resection following neo-adjuvant radio-chemotherapy (RCT) in patients with locally advanced non-small cell lung cancer (NSCLC) is yet not clearly defined. The aim of our study was to analyze the postoperative survival and to identify relevant prognostic factors. 46 patients underwent curative resections after neo-adjuvant RCT for locally advanced NSCLC (IIIA/IIIB) between February 2008 and February 2015. A retrospective data analysis regarding preoperative regression status, perioperative mortality, postoperative survival, patho-histological remission, relapse pattern and other prognostic factors was performed. A neo-adjuvant RCT with a median radiation dose of 50.4 [range, 45-60] Gy was performed in 44 (96 %) patients. Partial and/or complete regression was observed in 32 (70 %) patients. R0-resection was achieved in 44 (96 %) patients. The 30-day mortality was 4 % and the perioperative morbidity was 37 %. The overall and progression free 5-year survival rate was 47 % and respectively 45 % [in median 58 months]. The 5-year survival rate of 64 % in the "responder"-group was significantly better when compared with 24 % in the "non-responder"-group (p = 0.038). The tri-modality therapy improved the prognosis in patients with locally advanced NSCLC (stage IIIA/IIIB). The complete patho-histological remission is an important prognostic factor for better long term survival. Dividing the patients in "responder" and "non-responder" after neo-adjuvant RCT may have large therapeutically consequences in the future.
EVALuna2:6809